2009
DOI: 10.1007/s11701-009-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reconstruction and anterior suspension with single anastomotic suture in robot-assisted laparoscopic radical prostatectomy: a simple method to improve early return of continence

Abstract: Post-prostatectomy urinary incontinence is a major cause of morbidity from radical prostatectomy. Efforts have been made to develop techniques to hasten return of urinary control. Several authors have demonstrated improved early continence with anterior, posterior, or combined reconstruction of the urethral–pelvic attachments. In this study, we compare three-month urinary function and continence data for patients who underwent RALP with posterior reconstruction and anterior suspension with single anastomotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Three (1.3%) patients had bladder neck reconstruction and 23 (9.9%) patients underwent bilateral PLND. One-hundred and ninety-eight (85.4%) patients had bilateral and 20 (8.6%) had unilateral neurovascular bundles spared, while 15 (6.4%) patients did not undergo a nerve sparing procedure (Table II) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) days and median urethral catheter duration was 5.0 (5-34) days. One-hundred and twenty-eight (54.9%) patients had the catheter removed five days after surgery and six of 128 (4.7%) patients experienced temporary acute urinary retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three (1.3%) patients had bladder neck reconstruction and 23 (9.9%) patients underwent bilateral PLND. One-hundred and ninety-eight (85.4%) patients had bilateral and 20 (8.6%) had unilateral neurovascular bundles spared, while 15 (6.4%) patients did not undergo a nerve sparing procedure (Table II) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) days and median urethral catheter duration was 5.0 (5-34) days. One-hundred and twenty-eight (54.9%) patients had the catheter removed five days after surgery and six of 128 (4.7%) patients experienced temporary acute urinary retention.…”
Section: Resultsmentioning
confidence: 99%
“…Although long-term continence rates exceed 90% in most RALP studies, short-term continence is widely variable and quality-of-life studies have revealed that urinary incontinence is severely bothersome to patients in the initial post-treatment period (2). Several techniques have been proposed to facilitate the early recovery of continence following RALP (3)(4)(5)(6)(7). Two functionally independent areas have been delineated to be associated with the mechanisms of continence: the distal or external urethral sphincter and the proximal or internal urethral sphincter located at the bladder neck (8).…”
Section: Introductionmentioning
confidence: 99%
“…While six controlled studies were in favor of this technique in terms of shorter time to continence and significant proportions of continent men, [21][22][23][24][25][26] five studies, including a randomized controlled study, reported no role of PR in continence. 10,13,[27][28][29] Two recent systematic reviews showed no or only a slight benefit of PR in postoperative continence.…”
Section: Discussionmentioning
confidence: 99%
“…Dans 2 cas (7%), on a eu besoin de rajuster la tension des points de suture ou de placer des agrafes LapraTy (Ethicon Endo-Surgery, Cincinnati, OH) pour assurer une fermeture hermétique. Aucun patient n'a présenté de fuite urinaire clinique ni aucune rétention urinaire après le retrait du cathéter en moyenne 5 jours après l'opération (EIQ [4][5][6]. Conclusions : Selon notre expérience clinique, cette nouvelle technique de fermeture de plaie par le dispositif V-Loc pour une PRAR avec anastomose semble sans danger et efficace.…”
Section: Résuméunclassified
“…1 Numerous modifications have also been described to facilitate VUA, prevent anastomotic leaks and improve continence outcomes. [2][3][4][5][6][7] Despite techniques for posterior rhabdosphincter reconstruction (PR), limitations of the running monofilament reconstruction include loss of tension due to suture loosening. Back-slippage of tension is increased by the steep Trandelenburg position that naturally pulls the bladder away from the operative field.…”
Section: Introductionmentioning
confidence: 99%